“男扮女声”的心理机制探寻 ：唐代弃妇诗的一种考察 = Psychological motivation behind male authors’ writing from women’s perspective : a study on abandoned women in Tang poetry - 刘鹏程 Liu, Pengcheng (Nanyang Technological University, 2020)
弃妇诗即是描写弃妇感伤哀怨、自怜自叹以及其悲惨遭遇的诗歌，而唐代是弃妇诗的繁荣期。首先，笔者对先唐弃妇诗的演进，进行了必要的梳理，概括了弃妇诗在先唐时期的基本发展历程。然后，笔者借助西方心理学的“双性同体”与“阿尼玛”理论，考察了唐代男性诗人拟作闺音时的心理机制，并对两性闺音在创作上做出比较。最后，笔者通过与其他类型的怨情诗（宫怨诗、思妇诗）的对比，对弃妇诗的含义进行了再界定，并对唐代弃妇诗的社会价值提出了自己的见解。 Poetry of Abandoned Women describes the abandoned women’s thoughts and feelings after their tragic experiences, and Tang Dynasty is the prosperous period for Poetry of Abandoned Women. This paper first summarizes the evolution of the Poetry of Abandoned Women and then describes the historical trend of these poems in the Pre-Tang period. Next, the “Androgyny and Anima” Theories from western psychology are applied to investigate the psychological motivation behind male authors’ writing from woman’s perspective and the paper also compares the difference between the boudoir voice from both genders. Lastly, through the comparison to other types of Resentment Poetry (such as Poetry on Resentment of Palace Women and Poetry of Pining Women), the paper redefines the poetry of Abandoned Women and puts forth relevant insights on the social value of these poems.